Identification of unknown nuclear material - Fantidis, J. G.; Nikolaou, G. E.; Tsagas, F. N. (HNPS Advances in Nuclear Physics, 2020)
The identification of spent PWR nuclear fuel in terms of its initial enrichment and final burnup is demonstrated. Spent UO2 fuel from a PWR power station was used as the nuclear material of supposed unknown irradiation history. The identification procedure was based on determining the U and Pu isotopic composition of the fuel by chemical analyses, simulation calculations of fuel evolution and statistical analysis. The procedures followed and associated limitations are discussed.